Social isolation in adolescence and long-term changes in the gut microbiota composition and in the hippocampal inflammation: Implications for psychiatric disorders – Dirk Hellhammer Award Paper 2021. (November 2021) - Lopizzo, Nicola; Marizzoni, Moira; Begni, Veronica; Mazzelli, Monica; Provasi, Stefania; Borruso, Luigimaria; Riva, Marco Andrea; Cattaneo, Annamaria
Abstract: Exposure to early adverse experiences induces persistent changes in physiological, emotional and behavioural functions predisposing the individual to an enhanced vulnerability to develop different disorders during lifespan. The adverse outcomes depend upon the timing of the stressful experiences, and in this contest, adolescence represents a key sensitive period for brain development. Among the biological systems involved, gut microbiota has recently been proposed to act on the interplay between the stress response, brain functions and immune system, through the gut-brain axis communication. In the current study we aimed to evaluate, in a preclinical model, changes over time in the microbiota community structure in physiological condition and in response to stress during adolescence. We also aimed to correlate the microbiota composition to the inflammatory status in brain. We used the preclinical model of social deprivation in rats during adolescence, based on the lack of all social contacts, for four weeks after weaning, followed by re-socialization until adulthood. We collected fecal samples at different post-natal days to investigate the short- and long-lasting effects of social isolation on gut microbiota composition and we collected brain areas (dorsal and ventral hippocampus) samples at killing to measure a panel of inflammatory and microglia activation markers. 16 S metataxonomic sequencing analysis revealed that microbial changes were influenced by age in both isolated and controls rats, regardless of sex, whereas social isolation impacted the microbial composition in a sex-dependent manner. A multivariate analysis showed that social isolation induced short-term gut microbiota alterations in females but not in males. We also identified several stress-related genera associated with social isolation condition. In brain areas we found a specific inflammatory pattern, in dorsal and ventral hippocampus, that significantly correlated with gut microbiota composition. Overall, in this study we reported a novel sex-specific association between gut microbiota composition and inflammatory response related to social isolation paradigm during adolescence, suggesting that stressful experiences during this sensitive period could have a long-lasting impact on the development of different biological systems that could in turn influence the vulnerability to develop mental disorders later in life. Highlights: Early life stress (ELS) enhances vulnerability to develop disorders during lifespan. ELS in rats during adolescence induces microbiota changes and neuroinflammation. The degree of microbiota and inflammatory alterations differs according to sex. Stress-related gut microbial genera were associated with brain inflammation.